2018
DOI: 10.1111/liv.13988
|View full text |Cite
|
Sign up to set email alerts
|

Extent of portal vein tumour thrombosis in patients with hepatocellular carcinoma: The more, the worse?

Abstract: Background & Aims Portal vein tumour thrombosis (PVTT) has a significant impact on the prognosis of patients with hepatocellular carcinoma (HCC). The degree of PVTT varies from sub‐/segmental invasion to complete occlusion of the main trunk. Aim of this study was to evaluate whether the degree of PVTT correlates with prognosis. Methods A total of 1317 patients with HCC treated at our tertiary referral centre between January 2005 and December 2016 were included. PVTT was diagnosed by contrast‐enhanced computed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
61
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 33 publications
(60 reference statements)
3
61
0
Order By: Relevance
“…125 Interestingly, the presence of either MVI/PVTT or PVT is associated with poor survival in patients with HCC. 126 Studies have shown that for patients with PVTT, prognosis depends on grade, with median survivals of just 2-5 months reported in patients with PVTT of the main trunk. 126,127 Patients with HCC and diagnosed PVTT have advanced disease (BCLC stage C).…”
Section: Patients With Vascular Invasion or Portal Vein Thrombosismentioning
confidence: 99%
“…125 Interestingly, the presence of either MVI/PVTT or PVT is associated with poor survival in patients with HCC. 126 Studies have shown that for patients with PVTT, prognosis depends on grade, with median survivals of just 2-5 months reported in patients with PVTT of the main trunk. 126,127 Patients with HCC and diagnosed PVTT have advanced disease (BCLC stage C).…”
Section: Patients With Vascular Invasion or Portal Vein Thrombosismentioning
confidence: 99%
“…The extent of PVTT was classified as follows: Vp0, no PVTT; Vp1, segmental PV invasion; Vp2, right anterior or posterior PV; Vp3, right or left PV; and Vp4, main trunk and/or contralateral portal vein branch to the primarily involved lobe. 12,13,17 Inclusion criteria for TKI treatment were as follows: having metastatic or locally advanced HCC that was unresectable or refractory to transarterial chemoembolization with BCLC stage B or C 9 and Eastern Cooperative Oncology Group performance status 0 to 1. 26 The reasons why patients received additional therapy were mainly discontinuation of TKI therapy due to any unacceptable or serious adverse events (AEs) or tumor progression.…”
Section: Patientsmentioning
confidence: 99%
“…Regarding tumor PVTT, 224 (64.9%), 48 (13.9%), and 70 (20.2%) patients had Vp0, 1/2, and 3/4 as classified by previous reports. 12,13,17 Median TKI treatment duration was 115 days.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations